Efficacy and Safety of Lomitapide in Homozygous Familial Hypercholesterolaemia: A Systematic Review - Namin Wei; Yuanhui Hu; Siyu Li; Guoxiu Liu; Nang Zhang; Qiulei Jia; Jingjing Shi; Guozhen Yuan; Huaqiang Zhai (Reviews in Cardiovascular Medicine, 2022)
Background: Homozygous familial hypercholesterolaemia (HoFH) patients have little or no low-density lipoprotein receptor (LDLR) function. HMG-CoA (3-hydroxy-3-methyl glutaryl coenzyme A) reductase inhibitors (statins) and proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors have limited lipid-lowering effects, therefore, there is an urgent need to develop new HoFH treatments. In 2012, the US Food and Drug Administration (FDA) approved the administration of lomitapide for lowering low-density lipoprotein cholesterol (LDL-C) levels. However, lomitapide is associated with various gastrointestinal disorders, elevated hepatic alanine aminotransferase (ALT) levels and other adverse reactions, thus, its long-term efficacy and safety in pediatrics and adults should be evaluated. A systematic review conducted in 2017 reported the efficacy and safety of lomitapide in Family hypercholesterolaemia (FH) patients. In this systematic review, we elucidate on the efficacy and safety of lomitapide in HoFH patients. Methods: A search was conducted in PubMed, Embase, Web of Science and Cochrane library databases to identify valid studies involving lomitapide-treated HoFH patients published before 11th August 2021. Results: A total of 18 clinical studies involving 120 lomitapide-treated HoFH patients were identified. Lomitapide significantly suppressed LDL-C levels in HoFH patients. Clinical manifestations for lomitapide in children were comparable to those in adults. The most common adverse events were gastrointestinal disturbances and elevated ALT levels. However, most patients tolerated the treatment-associated adverse reactions. Low-fat diets and drug dose adjustments were appropriate measures for controlling the treatment-associated adverse reactions. Conclusions: In pediatric and adult HoFH patients, lomitapide significantly suppresses LDL-C levels, therefore, it is an important option for HoFH treatment. The most common adverse events of lomitapide treatment include gastrointestinal disorders and elevated hepatic ALT levels. Despite the limitations, lomitapide is feasible for long-term treatment of HoFH patients, with dietary and safety monitoring. Registration Number in PROSPERO: CRD42021284425.